Career Preparation Education for Students of Ahmad Yani Batang Islamic High School (Universitas Negeri Semarang, 2022)
The implementation of community service for Ahmad Yani Islamic High School students, Batang District, Batang Regency, collaborated with one of the management lecturers at Karangturi University, Semarang. Ahmad Yani Batang Islamic High School is a private high school located in the village of Dracik Kembang, Proyonanggan sub-district, Batang district. This private school, established in 1985, is headed by Mr Mohammad Akyas, M.Sc. The future is uncertain. High school students who are less fortunate to continue their studies to the tertiary level will choose to work. However, there are so many high school students who, when they leave school, do not have sufficient provisions to face the world of work. Therefore, it is necessary to assist these students in providing an initial picture of strategies for entering the world of work. Pelaksanaan pengabdian kepada masyarakat pada siswa SMA Islam Ahmad Yani Kecamatan Batang Kabupaten Batang berkolaborasi dengan salah satu dosen manajemen Universitas Karangturi Semarang. SMA Islam Ahmad Yani Batang adalah salah satu sekolah menengah swasta yang terletak di desa Dracik Kembang, kelurahan Proyonanggan kabupaten Batang. Sekolah swasta yang telah berdiri sejak tahun 1985 ini dikepalai oleh bapak Mohammad Akyas, M.Si. Masa depan adalah sesuatu hal yang tidak pasti. Para siswa SMA yang kurang beruntung untuk melanjutkan studi ke jenjang perguruan tinggi maka akan memilih untuk bekerja. Namun begitu banyak siswa SMA yang ketika lulus sekolah tidak memiliki bekal yang cukup untuk menghadapi dunia kerja. Oleh karena itu perlu untuk dilakukan pendampingan terhadap siswa-siswa tersebut guna memberikan gambaran awal mengenai strategi memasuki dunia kerja